Modelo para avaliação da capacidade de inovação do setor cooperativista - Penteado, Rosmeiri Aparecida Ribeiro Ferras (2025)
The aim of this thesis was to develop a specific model for measuring innovation capacity in the cooperative sector. The sample used in this study was agro-industrial cooperatives from Paraná, linked to Ocepar (Organization of Cooperatives of the State of Paraná). The research is based on the finding that, although there are models for measuring innovation in business environments, none are geared towards the specific characteristics of cooperatives, whose organizational structures, principles, and objectives differ substantially from traditional business models. To this end, the research adopts a mixed methodological approach, with qualitative and quantitative phases. Initially, a bibliometric analysis was carried out using the Methodi Ordinatio method, identifying the most relevant studies on models for measuring innovation capacity, according to InOrdinatio, in the literature. This survey identified existing models of corporate innovation capacity. With the insights generated by the studies and combined with the cooperative principles, a proposal was drawn up for the measurement instrument, based on dimensions, indicators, and descriptors. Next, interviews were conducted with experts in cooperative innovation to define and weight the most relevant variables in this model. The structure of the proposed model includes dimensions such as technology, products and processes, business strategy, people management, relationship network, organizational structure, corporate leadership, and results. The measurement is operationalized using the FSAW (Fuzzy Simple Additive Weighting) method, which allows multi-criteria weighting considering uncertainties and subjectivity. The model was applied to nine agro-industrial cooperatives in Paraná, enabling a comparative diagnosis of their capacity for innovation. The results show the applicability of the model as a tool to support management and decision-making, as well as demonstrating the importance of considering variables aligned with cooperative identity. The thesis contributes to scientific progress in the field of production engineering and provides a practical tool for institutions and managers who work to promote innovation in cooperatives.